A study on the common defects in primary school buildings / Norlaila Abd Nasir - Abd Nasir, Norlaila (Faculty of Architecture, Planning and Surveying, 2013)
Maintenance of the school building is a step that is not only going to affect the structure of the school building, environment, comfort and economy but also an impact on a student's safety. The greater the investment, the greater the interest and profit will be gained by the country in the future. The effectiveness of a maintenance system depends on the planning and understanding towards aspect and maintenance methods before the activity commences. Study and research should be carried out in terms of design, materials, skills, functions, requirements and relationships between them to determine the problem and the defect to the school building. In addition, safety and health, comfort, function and either the market value of the building or the consumer is also guaranteed. Referring to the British Standard 3811: 1984, maintenance is defined as combination of the technical and management aspects in all actions aimed at maintaining the function of an item, or restore it to its original function or condition. Referring to Burden (2004), a defect may be defined as a state that is not the same or irregular is happening and damage or weaken the strength of a building structure, durability or value. A housing or construction defect is a building flaw or design mistake that reduces the value of the home, and/or causes a dangerous condition. Some defects are obvious (such as water seepage) but many are less obvious and do not become apparent until years after a building was constructed.